Sharing Resource Wealth Inclusively Within and Across Generations - Pouokam, Nathalie (IMF Working Papers; Working Paper ;, 2021)
This paper discusses the main challenges faced by resource-rich nations in promoting equity; describes policy tools available for managing exhaustible natural resources; and analyzes the relationship between resource wealth and state fragility. It is argued that human capital accumulation, innovation, and technology diffusion can help escape the trap of low growth and resource dependence that plagues so many developing countries. But to make this possible, resource-rich nations must sustain strong citizen participation in the policy making to hold governments accountable and ensure the inclusive management of resource wealth.